2007
DOI: 10.1007/s00330-007-0602-5
|View full text |Cite
|
Sign up to set email alerts
|

Biliary and reticuloendothelial impairment in hepatocarcinogenesis: the diagnostic role of tissue-specific MR contrast media

Abstract: The development and progression of a hepatocellular carcinoma (HCC) in a chronically diseased liver, i.e., the carcinogenesis, comprise a multistep and long-term process. Morphologically, this process is associated with the presence of distinct nodular lesions in the liver that are called 'preneoplastic lesions.' These preneoplastic lesions are associated with and can precede the growth and progression of well-differentiated HCCs . The characterization of nodular lesions and demonstration of the multistep deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 75 publications
3
67
0
1
Order By: Relevance
“…THE LIVER-SPECIFIC MR contrast agent gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid (Gd-EOB-DTPA) (gadoxetic acid disodium, Primovist, Bayer Schering, Berlin, Germany) produces both dynamic and liver-specific hepatobiliary MR images (1)(2)(3)(4)(5)(6). This contrast agent is highly liver-specific; approximately 50% of the injected dose is taken up by functioning hepatocytes and is excreted in bile, as compared to an uptake of 3-5% for gadobenate dimeglumine (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…THE LIVER-SPECIFIC MR contrast agent gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid (Gd-EOB-DTPA) (gadoxetic acid disodium, Primovist, Bayer Schering, Berlin, Germany) produces both dynamic and liver-specific hepatobiliary MR images (1)(2)(3)(4)(5)(6). This contrast agent is highly liver-specific; approximately 50% of the injected dose is taken up by functioning hepatocytes and is excreted in bile, as compared to an uptake of 3-5% for gadobenate dimeglumine (4).…”
mentioning
confidence: 99%
“…This contrast agent is highly liver-specific; approximately 50% of the injected dose is taken up by functioning hepatocytes and is excreted in bile, as compared to an uptake of 3-5% for gadobenate dimeglumine (4). A bolus injection of gadoxetic acid provides a dual mode of action that allows imaging in the early dynamic phase (as with standard gadolinium chelates) and in the delayed phase (hepatobiliary phase) that is obtained 10 to 20 min after injection and lasts until 90 min after injection (7,8).…”
mentioning
confidence: 99%
“…The recently developed hepatobiliary agent, gadoxetic acid (Gadolinium-ethoxybezyl [Gd-EOB]-DTPA, Primovist, Bayer Schering Pharma, Berlin), is taken up preferentially by hepatocytes and evidences prolonged persistence in the liver, owing to the fact that approximately 50% of the injected dose is taken up by functioning hepatocytes and excreted in the bile, as compared with an uptake of 3-5% for gadobenate dimeglumine and hepatocyte-specific phase imaging after the injection of gadoxetic acid, which can be obtained earlier than gadobenate dimeglumine (13)(14)(15). Some investigators (16,17) have previously reported that gadoxetic acid-enhanced MRI allows for the accurate detection and characterization of focal liver lesions.…”
Section: Kjronlineorg 440mentioning
confidence: 99%
“…Gadoxetic acid (Eovist or Primovist, Bayer Schering: Berlin, Germany) has been approved for hepatic imaging and is being widely used (9)(10)(11)(12). It is a liver-specific hepatobiliary contrast agent which can also be used extracellularly.…”
Section: Introductionmentioning
confidence: 99%
“…It is a liver-specific hepatobiliary contrast agent which can also be used extracellularly. It is taken up by functioning hepatocytes and up to 50% is excreted into the bile (9,13). There have ) and dynamic gadoxetic acid-enhanced MRI as well as hepatobiliary phase were performed.…”
Section: Introductionmentioning
confidence: 99%